"Negative" diamagnetism of three‐dimensional arrays of semiconductor nano‐rings. Issue 10 (11th September 2013) - Thu, L. M.; Chiu, W. T.; Voskoboynikov, O.
<x xml:space="preserve">Abstract</x> We theoretically study the orbital diamagnetic response of three‐dimensional arrays of embedded InAs/GaAs wobbled nano‐rings. To simulate the rings' magnetic characteristics, we use the effective one band Hamiltonian (energy and position‐dependent electron effective mass and Landé factor) and smooth three‐dimensional confinement potential that is mapping the actual strain and material content inside the rings. First, we obtain the magnetic susceptibility of an individual nano‐ring. Once it is achieved, using the Claussius–Mossotti relation we estimate the effective susceptibility of three‐dimensional arrays of the rings. We show that conventionally diamagnetic InAs/GaAs ring structures under certain conditions can demonstrate the positive peak of the effective magnetic susceptibility of the arrays, that we call "negative"‐diamagnetic response. The "negative"‐diamagnetic (positive susceptibility) peak remains Lorentz‐like shaped and gradually disappears when the rings' concentration in the arrays decreases.